2019
DOI: 10.4236/tel.2019.95082
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measurement Model for Agriculture Extension Services for Sustainable Livelihood of the Farmers: Evidences from India

Abstract: Extensive services to agriculture are continuously evolving in less-developed economies like India. With a focus on productivity and farmers' livelihood improvement, Indian agriculture sector has witness a wide range of reforms in past decades. However, the unsustainable, fragmented and decentralized approach has attracted nationwide debate and criticism about the effectiveness of these reforms. In this study, empirically at the micro level, we investigated the impact of the government reforms and initiatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These results, meetings, and demand for service indicators are consistent with farmers’ perception of adopting no-till tillage in South Africa [ 52 ], satisfaction with extension services in Ethiopia [ 51 ], and adaptation to climate change in Ghana [ 59 ]. Equally, Joshi and Narayan [ 73 ] found that the frequency of extension contact is a significant indicator in the performance measurement of agricultural extension in sustainable livelihoods in India.…”
Section: Resultsmentioning
confidence: 99%
“…These results, meetings, and demand for service indicators are consistent with farmers’ perception of adopting no-till tillage in South Africa [ 52 ], satisfaction with extension services in Ethiopia [ 51 ], and adaptation to climate change in Ghana [ 59 ]. Equally, Joshi and Narayan [ 73 ] found that the frequency of extension contact is a significant indicator in the performance measurement of agricultural extension in sustainable livelihoods in India.…”
Section: Resultsmentioning
confidence: 99%
“…The production from the agriculture industry rises as the global population continues to grow (Verma 2018). Efficiency of the agriculture industry is commonly related to the improvement of livelihood for the rural population (Joshi and Narayan 2019). The agricultural activities include farming and livestock production and have a vital role in improving the nation's economy (Praburaj 2018).…”
Section: Livelihood Improvements Climate Action and Land Restorationmentioning
confidence: 99%
“…The respondent farmers were asked to indicate their agreement or disagreement on a five-point scale; strongly agree (5), agree (4), moderately agree (3), neutral (2) and disagree (1) for each statement. Likert type scales have been used to assess farmer's satisfaction of extension services by several studies (Joshi & Narayan, 2019, Elias et al, 2015, Ganpat et al, 2014. The respondent farmers were also asked to indicate their satisfaction to the overall process of agricultural service provisions initiated by local level governments.…”
Section: Study Sitementioning
confidence: 99%
“…Over the past ten years, several studies have been undertaken regarding farmers' satisfaction with the public agriculture extension services (Ganpat et al, 2014;Elias et al, 2015;Kassem et al, 2021) and their effectiveness (Debnath et al, 2016;Resnick, 2018;Joshi & Narayan, 2019). Findings of these studies indicated mixed results.…”
Section: Introductionmentioning
confidence: 99%